Performance Evaluation of Calypso® 4D Localization and Kilovoltage Image Guidance Systems for Interfraction Motion Management of Prostate Patients - Tomi Ogunleye; Peter J. Rossi; Ashesh B. Jani; Tim Fox; Eric Elder (The Scientific World Journal, 2009)
Prostate cancer represents a model site for advances in understanding inter- and intrafraction motion for radiotherapy. In this study, we examined the correlation of the electromagnetic transponder system/Calypso® 4D Localization System with conventional on-board imaging (OBI) using kilovoltage imaging. Initially using a quality assurance (QA) phantom and subsequently using data of seven patients, the vector distances between Calypso- and OBI-recorded shifts were compared using the t-test. For the 30 phantom measurements, the average differences between the measured Calypso offset and the calculated OBI shift were 0.4 ± 0.4, 0.2 ± 0.3, and 0.4 ± 0.3 mm in the lateral, longitudinal, and vertical directions, respectively (p = 0.73, p = 0.91, and p = 0.99, respectively), and the average difference vector for all sessions was 0.8 ± 0.4 mm. For the 259 patient measurements, the average differences between the measured Calypso offset and the calculated OBI shift were 0.7 ± 0.5, 1.1 ± 0.9, and 1.2 ± 0.9 mm in the lateral, longitudinal, and vertical directions, respectively (p = 0.45, p = 0.28, and p = 0.56, respectively), and the average difference vector for all sessions was 2.1 ± 1.0 mm. Our results demonstrated good correlation between Calypso and OBI. While other studies have explored the issue of Calypso/OBI correlation, our analysis is unique in our use of phantom validation and in our performing the patient analysis on an initial population prior to routine setup using Calypso without OBI. Implications for Calypso's role as a QA tool are discussed.